2022
DOI: 10.33394/jo-elt.v9i1.4425
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Media Edpuzzle and Its Implementation in Teaching Vocabulary in New Normal Era

Abstract: The aim of this study was to describe the use of interactive media EdPuzzle in teaching vocabulary. Many students had difficulties finding the right vocabulary in conveying ideas because the learning media used by the teacher was not varied. In new normal era, the teacher must be good at choosing interactive media for teaching vocabulary. One of interactive media was EdPuzzle, because it could make the learning process to become interesting. This study was quantitative descriptive. The research subject was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…After the course, the instructor will guide students in reaching a consensus on certain discoveries. (Rahayu & Bhaskoro, 2022) Based on the concerns and previous research findings, vocabulary-learning For teaching vocabulary, techniques utilizing interactive media, such EdPuzzle, were significant. In light of this, this study aimed to illustrate how junior high school students use the interactive medium EdPuzzle to acquire vocabulary.…”
Section: Fig 1 Digital Interactive Media Edpuzzle Applicationmentioning
confidence: 97%
See 1 more Smart Citation
“…After the course, the instructor will guide students in reaching a consensus on certain discoveries. (Rahayu & Bhaskoro, 2022) Based on the concerns and previous research findings, vocabulary-learning For teaching vocabulary, techniques utilizing interactive media, such EdPuzzle, were significant. In light of this, this study aimed to illustrate how junior high school students use the interactive medium EdPuzzle to acquire vocabulary.…”
Section: Fig 1 Digital Interactive Media Edpuzzle Applicationmentioning
confidence: 97%
“…Critical thinking skills are crucial for English acquisition. (Rahayu & Bhaskoro, 2022). Teachers want pupils to be able to communicate politely orally and in writing for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Education is hard to imagine organization without computer and internet access. Use it the internet and computers have brought us great changes (Leksono et al, 2020;Rahayu & Bhaskoro, 2022;Sułkowski et al, 2021). Students are clearly influenced and interested in the technology that has powered the world the latest technology products.…”
Section: Introductionmentioning
confidence: 99%
“…Flamboyan & Lestari (in Wahyudi, 2020) found that the teacher needed to find the appropriate media to allow students to practice speaking without pressure. (Rahayu & Bhaskoro, 2022) Discovered interactive multimedia incorporated into the instructional and educational experience can prevent students from becoming disinterested. Moreover, To Su & Cheng, (Redjeki & Muhajir, 2021) Applying game design concepts and mechanics in quasigame environments aims to involve individuals and resolve issues.. (Anisa et al, 2020) a gamification is a form of digital competence in which many levels of meaning are formed and processed through a playful application such as media.…”
Section: Introductionmentioning
confidence: 99%